Perfectionism and sleep disturbance - Azevedo, Maria Helena Pinto de (2009)
The main purpose of the present research was to explore gender-related associations between sleep disturbance and perfectionism dimensions in a large sample of undergraduate students. Perfectionism dimensions have been assessed using the Portuguese version of the Multidimensional Perfectionism Scale (Hewitt and Flett, 1991, J Pers Soc Psychol 60:456; Soares et al., 2003, Rev Port Psicossom 5:46) and sleep disturbance with two items concerning difficulties initiating sleep and difficulties maintaining sleep. A total of 1163 undergraduate students of both genders between 17 and 25 years of age completed the scale. Results from correlational and categorial analyses indicated that socially prescribed perfectionism was the only dimension associated with sleep disturbance in undergraduate students of both genders. Males with the highest levels of socially prescribed perfectionism were approximately twice more likely to report sleep disturbances than those with less socially prescribed perfectionism. Similar results were found within the female sample. Implications for future research and clinical practice are discussed.